Immediate effect of lower extremity joint manipulation on a lower extremity somatosensory illusion: a randomized, controlled crossover clinical pilot study - Schueren, Shannon; Hunger, Hugh; Pham, Huong; Smith, Dean L.; Layne, Charles; Malaya, Christopher A. (Frontiers in Human Neuroscience, 2022)
Objective: This study explored the influence of lower extremity manipulation on the postural after-effects of standing on an inclined surface. Methods: 8 healthy individuals (28.0 ± 4.1 years) were recruited for this open-label, crossover study. Participants stood on an incline board for 3 minutes to develop a known form of somatosensory illusion. After randomization to either a lower-extremity joint manipulation or no intervention, participants immediately stood on a force plate for 3 minutes with eyes closed. After a 24-hour washout period, participants completed the remaining condition. Center of pressure (CoP) position data was measured by a force plate and evaluated using statistical parametric mapping. Pathlength, mean velocity and RMS were calculated for significant time periods and compared with corrected, paired t-tests. Registered at ClinicalTrials.gov; NCT Number: NCT05226715 Results: Parametric maps revealed that CoP position of control and intervention conditions differed significantly for two time periods (70-86 seconds - control: 0.17±1.86 cm / intervention: -1.36±1.54 cm; 141-177 seconds – control: -0.35±1.61 cm / intervention: -1.93±1.48 cm). CoP pathlength was also significantly decreased for the second period (control: 6.11±4.81 cm / intervention: 3.62±1.92 cm). Conclusion: These findings suggest that extremity manipulation may be a useful intervention for populations where CoP stability is an issue. This study contributes to the growing body of evidence that manipulation of the extremities can drive global postural changes, as well as influence standing behavior. Further, it suggests these global changes may be driven by alterations in central integration.